Quantitative analysis of borax in sape crackers in Soro Village, Lambu District, Bima Regency - Nurhidayah, Nurhidayah; Wahyuningsih, Sri; Nisaatun, Khairatun (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Crackers are a popular snack product and have long been known by the people of Indonesia as a complement to meals that are often not left behind; without these snacks, people often feel something is missing in their diet. Manufacturers often misuse sodium tetraborate as white crystals with the chemical formula Na2B4O7. This quantitative research uses an experimental method using four samples of sape crackers. This research aims to determine the sape crackers in Soro village, Lambu subdistrict, Bima regency. Quantitative analysis of borax in the sape cracker sample was 9.67 µg/mL in sample A, 12.17 µg/mL in B sample, 13.89 µg/mL in the C sample, and 62.01 µg/mL in the D sample. This study concludes that the sape crackers produced in Soro Village, Lambu District, Bima Regency, from the four samples studied, were all positive for containing borax. It is hoped that producers can use permitted food additives such as Sodium Tripolyphosphate (STPP).